Presidential Veto on the Draft Constitution of the Democratic Republic of Timor Leste - Francisco Amaral Da Silva; Yohanes Usfunan; Putu Gede Arya Sumerta Yasa; I Nyoman Suyatna (Universitas Bali Dwipa, 2025)
This study aims to analyze and examine the President's Veto Rights over draft laws submitted by the Timor Leste Parliament. In the administration of the Democratic Republic of Timor Leste, it is stated in Article 74 of the 2002 Constitution of the Democratic Republic of Timor Leste (RDTL) that the President of the Republic is the Head of State and the symbol of the guarantor of national independence and national unity as well as the smooth functioning of state institutions in a democratic manner. So that the power / authority of the state is held by the President. The research method used in this study is the normative legal research method, which examines and examines based on book reviews / literature reviews and law reviews. The results of the study show that based on Article 85 of the 2002 Constitution of the Democratic Republic of Timor Leste (RDTL) states that one of the authorities of the President of the Democratic Republic of Timor Leste is the veto right over Draft Laws. The veto right is the right to cancel decisions, provisions, draft regulations and laws, or resolutions. In order to improve and make effective the oversight function of the national parliament in fighting for the aspirations of the people of the Democratic Republic of Timor Leste to protect human rights, it is necessary to have limitations and criteria for the use of the President's veto power over draft laws.